Improving Students' Vocabulary by Using Bingo Game at the Eighth Grade of SMP Swasta Idanoi in 2022/2023 - Hendrik Gea (English Education Department at FKIP Nommensen University, 2023)
Vocabulary is the words that has a meaning and used by people to communicate with other and it support skills in English, namely Listening, Speaking, Reading, and Writing. In the reality, the students at the Eighth grade of SMP Swasta Idanoi had a problem in vocabulary that effected in their Writing skill, namely: students were not able to know the English words and uses, students were not able to recognize the translation words and difficulties in memorizing the long syllable and unfamiliar words. Based on the problem, this research aimed to overcome the problem by using Bingo game. This research used Classroom Action Research (CAR) that consists of Planning, Action, Observation, and Reflection. The result of the research in cycle I showed there were 13 students did not pass the MCC of 21 students and the average of students’ mark was 63. The lowest score was 10 and the highest was 90. In the cycle II, all the students passed the MCC with the average of students’ mark was 93,33 with the lowest score was 80 and the highest score was 100. The researcher concluded Bingo game improved students’ vocabulary and overcome the students’ problem in this research.